2022
DOI: 10.3390/polym14153063
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Filler Loading and Alkaline Treatment on the Mechanical Properties of Palm Kernel Cake Filler Reinforced Epoxy Composites

Abstract: The manufacturing of materials, in conjunction with green technology, emphasises the need to employ renewable resources to ensure long-term sustainability. Re-exploring renewable elements that can be employed as reinforcing materials in polymer composites has been a major endeavour. The research goal is to determine how well palm kernel cake filler (PKCF) performs in reinforced epoxy composites. In this study, PKCF with 100 mesh was mixed with epoxy resin (ER) in various ratios ranging from 10% to 40% by weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…Alkali treatment improves the cleanliness and alters the surface of the PALF, which enhance its ability to stick or adhere to the tapioca biopolymer (TBP). [26][27][28] However, applying 5% (w/v) alkali treatment with 1 h immersion duration does not significantly improve the tensile performance of 30% of PALF reinforced TBP composites, which can only enhance 2.8% the improvement of tensile properties. 29 On the contrary, it has been demonstrated that incorporating a coupling agent can effectively augment the interfacial adhesion of the composite material.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Alkali treatment improves the cleanliness and alters the surface of the PALF, which enhance its ability to stick or adhere to the tapioca biopolymer (TBP). [26][27][28] However, applying 5% (w/v) alkali treatment with 1 h immersion duration does not significantly improve the tensile performance of 30% of PALF reinforced TBP composites, which can only enhance 2.8% the improvement of tensile properties. 29 On the contrary, it has been demonstrated that incorporating a coupling agent can effectively augment the interfacial adhesion of the composite material.…”
Section: Introductionmentioning
confidence: 98%
“…A prior investigation examined the employment of alkali treatment and coupling agents to enhance the interfacial adhesion and mechanical properties of composites made from PALF‐TBP. Alkali treatment improves the cleanliness and alters the surface of the PALF, which enhance its ability to stick or adhere to the tapioca biopolymer (TBP) 26–28 . However, applying 5% (w/v) alkali treatment with 1 h immersion duration does not significantly improve the tensile performance of 30% of PALF reinforced TBP composites, which can only enhance 2.8% the improvement of tensile properties 29 …”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites, composed of a polymer matrix and reinforcing fillers, are frequently utilized in the construction, packaging, consumer products, automotive, and aerospace industries, among other areas. 1,2 Due to their inherent characteristics, such as those of glass fiber and carbon fiber, common synthetic fillers have restrictions on their impact on the environment and the availability of resources. Moreover, investigating natural fillers as reinforcement in polymer composites has progressed in engineering and material science.…”
Section: Introductionmentioning
confidence: 99%
“…For composite materials to be properly tailored to meet application requirements, it is essential to understand the mechanisms by which these constituents interact. 1,7,8 Furthermore, the size of the filler particles has an impact on the composite's mechanical properties. Fillers that are nanoscale in size have a high surface area-to-volume ratio, which improves molecular reinforcement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation